Performance of marine and offshore paint systems: Correlation of accelerated corrosion tests and field exposure on operating ships. Issue 3 (10th December 2013) - LeBozec, N.; Thierry, D.; Le Calvé, P.; Favennec, C.; Pautasso, J.‐P.; Hubert, C.
Abstract : Corrosion resistance is an important property requirement for marine paint systems used in naval industry such as for ship's topsides and superstructures, which obliges testing the coating performance in order to make a durable selection of the paint systems. This can be achieved by performing laboratory accelerated corrosion tests recommended for C5M corrosivity class (in particular the standard neutral salt spray test ISO 9227 or the cyclic corrosion test ISO 20340‐Annex A) which give results in a rather short delay (up to 6 months) compared to field exposures in marine atmospheres (several years). It is however well known that these tests may not be fully representative of real ship environmental conditions. The aims of the present study were thus to compare and estimate the correlation of various accelerated corrosion tests including standardized tests (ISO 9227, ISO 20340, ISO 16701) and newly developed test conditions to field exposures on worldwide operating ships (container carrier vessel and oceanographic ship) and on conventional static marine atmospheric sites (C5M). Fifteen different marine paint systems commonly used for offshore and naval application were selected for the study. From the results, the exposure conditions on the container vessel were the most aggressive ones compared to static exposures after 2 years. The best correlation to such field exposure was observed using the cyclic test ISO 16701 with a deviation inferior to 25%, an acceleration factor of 4 and comparable corrosion aspect. If all testing conditions involving NaCl 5 wt% (including ISO 20340) showed a superior acceleration factor (e.g., about 12), a larger deviation (50%) was however found indicating that these tests did not accelerate the corrosion degradation of the paint systems similarly to field exposures. In addition, conditions for an optimization of ISO 20340 annex A test were found.